Triterpenoids from the Stem Bark of Crataeva nurvala (Dhaka University Journal of Pharmaceutical Sciences, 2008)
Two triterpenoids, phragmalin triacetate (1) and lupeol (2) were isolated from an ethyl acetate extract of the stem bark of Crataeva nurvala (Capparidaceae) by repeated chromatography over silica gel. The structures of these compounds were determined by spectroscopic analyses (UV, IR, 1H NMR, 13C NMR and EIMS). This is the first report of the systematic phytochemical investigation and the presence of these compounds 1 and 2 from this plant. Key words: Crataeva, Capparidaceae, Phragmalin triacetate and Lupeol. Â DOI = 10.3329/dujps.v7i1.1221 Dhaka Univ. J. Pharm. Sci. 7(1): 71-74, 2008 (June)